67.8k views
1 vote
Super confused help need answer soon

Which of the following correctly simplifies the expression



3 to the power of 2 multiplied by 1 whole over 4, the whole squared. = 3 to the power of 1 multiplied by 1 squared over 4 squared. = 1 over 6.
3 to the power of 2 multiplied by 0 whole over 4, the whole squared. = 3 to the power of 4 multiplied by 0 over 4 squared. = 0
3 to the power of 2 multiplied by 0 whole over 4, the whole squared. = 3 to the power of 1 multiplied by 0 over 4 squared. = 0
3 to the power of 2 multiplied by 1 whole over 4, the whole squared. = 3 to the power of 4 multiplied by 1 squared over 4 squared. = 81 over 16.

Super confused help need answer soon Which of the following correctly simplifies the-example-1
User Jasson
by
5.8k points

1 Answer

2 votes
you multiply the first number by the bottom them add the last numbers & then you divide your first answer by 2 and it should give you your answer !


User Mian Majid
by
6.0k points